1999
DOI: 10.1034/j.1399-3003.1999.14b05.x
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive measurement of respiratory muscle performance after exhaustive endurance exercise

Abstract: The use of noninvasive techniques to measure respiratory muscle performance after different types of endurance exercise has not been entirely successful, as the results have not consistently indicated diminished performance for similar types of exercise. The aim of the present study was 1) to compare different, noninvasive methods to assess respiratory muscle performance before and after an exhaustive cycling endurance test (which has previously been shown to induce diaphragmatic fatigue) and 2) to determine w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0
1

Year Published

2002
2002
2007
2007

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 20 publications
2
19
0
1
Order By: Relevance
“…Similar to previous studies (O 'Kroy et al 1992;Perret et al 1999), intensive exercise per se did not induce a signiWcant change in PI max (CON-EX). However, PI max was reduced by 7% after expiratory resistive breathing.…”
Section: Methodological Aspectssupporting
confidence: 79%
See 1 more Smart Citation
“…Similar to previous studies (O 'Kroy et al 1992;Perret et al 1999), intensive exercise per se did not induce a signiWcant change in PI max (CON-EX). However, PI max was reduced by 7% after expiratory resistive breathing.…”
Section: Methodological Aspectssupporting
confidence: 79%
“…In the course of exhaustive high-intensity exercise (¸85% of maximal oxygen consumption), inspiratory muscles are known to fatigue (Johnson et al 1993;Mador et al 1993;Perret et al 1999Perret et al , 2000 but also, expiratory muscle fatigue (EMF) was recently shown to develop under similar conditions (Taylor et al 2006;Verges et al 2006b). Expiratory muscles may be even more prone to fatigue than inspiratory muscles as several studies have shown that expiratory muscles are in general less oxidative than S. Verges · Y. Sager · C. Erni · C. M. Spengler Institute of Physiology and Center for Integrative Human Physiology (ZIHP), University of Zurich, Zurich, Switzerland inspiratory muscles (Lieberman et al 1973;Uribe et al 1992) and are therefore expected to be less fatigue resistant.…”
Section: Introductionmentioning
confidence: 99%
“…However, these findings are still disputed. A number of studies have not been able to show these similar results (Coast et al 1990;Johnson et al 1993;Perret et al 1999). Also, whole body endurance exercise in healthy subjects has been shown to cause diaphragmatic fatigue in a wide range of fitness levels (Johnson et al 1993).…”
Section: Exercise-induced Imf and The Implications Of The Timeline Fomentioning
confidence: 80%
“…Taking into account these points the question still remains of whether task failure, under these conditions, is a good measure for inspiratory muscle fatigue. We previously found that subjects breathing at a constant load ($80% maximal inspiratory pressure; MIP) with paced respiratory frequency (f R ) and duty cycle until task failure can breathe for the same duration with only a 15-min break after the first run (Perret et al 1999).…”
Section: Introductionmentioning
confidence: 99%